2‐Hydroxymelatonin promotes the resistance of rice plant to multiple simultaneous abiotic stresses (combined cold and drought). Issue 3 (1st July 2016) - Lee, Hye‐Jung; Back, Kyoungwhan
Abstract: We investigated the physiological roles of 2‐hydroxymelatonin (2‐OHMel) in rice seedlings. When they were challenged with simultaneous multiple abiotic stressors, such as a combination of cold and drought, those pretreated with 2‐OHMel were resistant, whereas no tolerance was observed in seedlings treated with either melatonin or water (control). The tolerance phenotype was associated with the induction of several transporter proteins, including the proton transporter ( UCP1 ), potassium transporter ( HKT1 ), and water channel protein ( PIP2;1 ). Treatment with 2‐OHMel increased the content of the osmoprotectant proline and maintained mitochondrial structure when plants were subjected to a combination of cold and drought stress. We screened the corresponding transcription factors (TFs) for 2‐OHMel‐mediated resistance to the combined stressors through analysis of large numbers of cold‐ and drought‐related TFs. Two TFs, Myb4 and AP37, were only induced by 2‐OHMel treatment. Transgenic rice lines overexpressing rice Myb4 were not resistant to the combined stressors; however, the expression of UCP1, HKT1, and PIP2;1 transcripts was slightly enhanced. These data show that 2‐OHMel alleviates the effects of simultaneous abiotic stressors via the actions of multiple TFs, including Myb4 and AP37 .